The Effectiveness of Mathematics Learning Media Developed with Artificial Intelligence (AI) Assistance in Training Basic Arithmetic Skills - Husnu Athoillah; Risma Firda Diana (Al-Qalam Institute, 2026)
Limited integration of artificial intelligence into elementary mathematics instruction continues to constrain opportunities for students to develop basic arithmetic skills through engaging learning experiences. Addressing this challenge, the present study examined the effectiveness of AI-assisted mathematics learning media developed through the pedagogical integration of ChatGPT and Canva AI for second-grade students. A quantitative pre-experimental approach employing a one-group pretest-posttest design was implemented with 25 participants selected through purposive sampling. Data were collected using expert validation sheets and students' arithmetic achievement tests. The learning media and assessment instruments were first evaluated for validity, after which students completed pretest and posttest assessments. Data analysis was performed using descriptive statistics, normality testing, and the Wilcoxon Signed-Rank Test. Expert evaluation classified both the learning media and the assessment instrument as highly valid, confirming their suitability for classroom implementation. Students' arithmetic achievement improved significantly following the intervention, demonstrating that the developed learning media effectively strengthened basic arithmetic skills. These findings indicate that the educational value of generative AI extends beyond content generation by supporting the design of interactive, visually engaging, and learner-centered mathematics instruction. Integrating ChatGPT and Canva AI therefore represents a promising instructional approach for enhancing foundational numeracy learning in elementary education.